Pemanfaatan Gedung Bersejarah Werenhuis dan Istana Maimun sebagai Sumber Belajar Bagi Siswa di SMA Al-Washliyah 1 - Gulo, Oktavianus; Hadiani Fitri; Pulung Sumantri (Islamic Education, 2023)
The aim of this research is to find out the historical buildings in Medan. Historic buildings are buildings that have ornaments that are no longer used in new buildings today and have a history that was influential in the era when the building was built. Learning resources are anything that can be used to facilitate all learning activities individually or in combination and to help someone achieve the desired learning goals. The type of research method used is descriptive qualitative research. Efforts to create historical learning resources effectively and optimally are by utilizing learning resources around students. One of them is the use of the Maimun Palace Building and the Warenhuis Building which aims to strengthen students understanding of local history. Local historical events are very important to study, especially to get to know the nation. The environment around students contains evidence of historical events which can help teachers to develop students' understanding of the past and make students understand that history is not just a story, but is an event that really happened at that time.